(3JfhjQ GdCHUGQ hLGeY GdHMGQs - (3GdNWjH GdJeQJGTj , eMeO Hf YHO Gddg Hf CMeO Hf EHQGgje Hf JeQJGT GdZRj GdMfaj, TeS GdOjf,J (B1004 (3g` s ((3eMeO Hf MGeO Hf Ydi egjGQ s)
(3ChdgG (B:s
(3hEf de jcf CgdkG ddcaGdI dchfgG dGJbJVi GdcaGdI Hd GdhcGdI s
(3BNQgG (B:s
(3bGd eDdag QMeg Gddg JYGdi ajG TQai Ef cfJ QHi bHdJg hEf cGf cd GdfGS QOhg Yf MSO aJbHdfi hJMTQfG LeYkG eY GdeUWai CMeO hENhGffG WGdH GdQTO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B196s
Keywords: (3Gdabg GdMfajs